Shikonin as a therapeutic agent in renal cell carcinoma: insights from TEK-related causal association with glaucoma - Jia, Ruyue; Liang, Yiran; Zou, Benkui; Li, Xiangzhi; Chen, Tao; Zhang, Chao; Bian, Jiasheng; Guo, Renbo (Frontiers in Pharmacology, 2025)
IntroductionRenal cell carcinoma (RCC) is a lethal malignancy with rising incidence, while glaucoma, a chronic eye disease, shares systemic mechanisms such as oxidative stress and inflammation with cancers. This study aimed to investigate the causal link between glaucoma and RCC and explore molecular intersections to identify novel therapeutic targets.MethodsA two-step Mendelian randomization (MR) analysis using genetic data from the NHGRI-EBI GWAS Catalog and FinnGen database was performed, supplemented by NHANES data. Gene expression analysis (GSE53757, E-MTAB-1980) identified glaucoma-related genes in RCC. Molecular docking and functional assays evaluated shikonin's effects on TEK and AKT/mTOR signaling.ResultsMR revealed a significant causal relationship between glaucoma and RCC. TEK, a glaucoma-related gene, was downregulated in RCC tissues and correlated with advanced tumor stage and metastasis. Shikonin and acetylshikonin upregulated TEK expression, inhibited RCC cell proliferation/migration, and suppressed AKT/mTOR phosphorylation.DiscussionThese findings support a role for glaucoma-associated genes in RCC development and progression, highlighting shikonin as a promising therapeutic agent targeting this molecular axis.